Conductive slurry composition and application thereof
By adding bicarbonate to the conductive paste and using glass powder of different particle sizes, the particle settlement problem caused by the reduction of viscosity of the high-temperature cured conductive paste is solved, and the stability and uniformity of the conductive lines are improved.
Patent Information
- Application Number
- CN202411846696.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-18
AI Technical Summary
The viscosity of the conductive paste cured at high temperature becomes lower when the temperature rises, resulting in the settlement of glass powder and conductive particles, affecting the conductivity and uniformity.
Bicarbonate is added to the conductive paste, which decomposes and releases gas within a certain temperature range, forming tiny bubbles, preventing particles from settling, and using glass powder of different particle sizes to improve the adaptability of the melting temperature.
Through the combination of bicarbonate gas generation and glass powder of different particle sizes, the particle settlement of the conductive paste during heating is avoided, the uniformity of the paste is maintained, and the conductivity and uniformity of the conductive lines are improved.
Smart Images

Figure CN119650137A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of conductive pastes and relates to a conductive paste composition and application thereof. Background Art
[0002] Conductive paste is generally composed of conductive particles, organic binders and other components. Other ingredients will be added according to different application occasions, curing temperature, etc. For example, conductive paste applied to silicon-based substrates needs to add glass powder to achieve melting of glass powder and fusion with silicon-based substrate at high temperature to form a highly adherent conductive circuit. For conductive pastes that cure at lower temperatures (curing temperature generally does not exceed 200°C), the formation of conductive circuits and adhesion to the substrate are generally achieved through the curing of the binder; for conductive pastes that cure at high temperatures (curing temperature generally around 600°C), they mainly rely on the melting of glass powder and bonding to the substrate, and the organic components (such as binders, etc.) therein need to be volatilized or decomposed and removed as much as possible. Therefore, the raw material composition of conductive pastes that cure at lower temperatures and conductive pastes that cure at high temperatures is significantly different. For example, the conductive paste disclosed in Chinese patent CN113555145A belongs to a conductive paste cured at a relatively low temperature, comprising 50-90% conductive powder, 5-45% high heat-resistant resin, 1-20% epoxy resin, 0.1-20% curing agent, 0.05-1% accelerator, 0.5-3% toughening agent, 1-20% solvent, 0.01-1% coupling agent and 0.01-1% rheological additive, and the toughening agent comprises aminosilicone oil modified epoxy resin obtained by reacting aminosilicone oil and epoxy resin. For conductive paste cured at high temperature, it is disadvantageous to add curing agent and toughening agent, which is not conducive to subsequent removal, otherwise it will affect the conductivity of the circuit. However, for high-temperature cured conductive paste, as the temperature rises, the viscosity of the paste will decrease rapidly before the organic components are removed, which may cause the glass powder, conductive particles, etc. in the paste to settle to varying degrees. The uniform conductive paste will become uneven, affecting the conductivity of the cured circuit, causing the conductivity to deteriorate and / or become uneven.
[0003] Therefore, the above problems need to be solved urgently. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a conductive paste composition and application thereof.
[0005] The technical solution of the present invention is as follows:
[0006] A conductive paste composition comprises, by weight, 100%, 50-85% conductive powder, 1-6% epoxy resin, 10-15% polyimide resin, 1-5% solvent, 1-5% glass powder, 1-10% bicarbonate and 0.5-3% rheological additive.
[0007] Preferably, the conductive powder is selected from one or a combination of two or more of silver powder, silver-coated copper powder, copper powder, nickel powder, aluminum powder, silver-coated nickel powder and silver-coated aluminum powder.
[0008] Preferably, the average particle size of the conductive powder is 0.5-10 μm.
[0009] Preferably, the initial melting temperature of the glass powder is not less than 450°C.
[0010] Preferably, the glass powder consists of a first glass powder and a second glass powder;
[0011] The particle size of the first glass powder is 400-500 mesh, and the particle size of the second glass powder is 1000-2000 mesh.
[0012] More preferably, the weight ratio of the first glass powder to the second glass powder is 1-10:1.
[0013] Preferably, the bicarbonate is selected from one or a combination of two or more of sodium bicarbonate, potassium bicarbonate, ammonium bicarbonate, magnesium bicarbonate and calcium bicarbonate.
[0014] Preferably, the raw material components further include one or a combination of two or more of 0.2-1% defoamer, 0.3-1% coupling agent and 0.2-1% curing agent.
[0015] Preferably, the curing agent is selected from imidazole compounds.
[0016] The conductive paste composition described in any of the above technical solutions is applied to silicon-based circuit boards.
[0017] The beneficial effects of the present invention are:
[0018] (1) In order to prevent the viscosity of the conductive paste from decreasing due to temperature increase, which may lead to different degrees of sedimentation of glass powder, conductive particles, etc., bicarbonate is added to the conductive paste of the present invention. Bicarbonate will gradually decompose and release gas to form tiny bubbles within a certain temperature range. The generation and rising process of the tiny bubbles will form disturbances and hinder the sedimentation of glass powder, conductive particles, etc., so that the conductive paste does not cause sedimentation of particles during the heating process, thereby maintaining the uniformity of the paste.
[0019] (2) The glass powder of the present invention is composed of two glass powders with different particle sizes. The glass powder with a small particle size (the second glass powder) has a lower melting temperature and can be melted at a lower temperature to form a preliminary bond with the substrate. It is also graded with the glass powder with a large particle size (the first glass powder) and provides a melting temperature range that is more compatible with the sintering temperature of the slurry (about 600°C), which is beneficial to the formation and non-deformation of the conductive circuit. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a circuit picture after the conductive paste obtained in Example 3 is printed and sintered and cured. DETAILED DESCRIPTION
[0021] The technical solution of the present invention is further illustrated and described below through specific implementation methods.
[0022] In order to improve the stability of the conductive paste during the heating process and avoid the sedimentation of particles, on the one hand, the present invention provides a conductive paste composition, which comprises, by weight, 100%, 50-85% conductive powder, 1-6% epoxy resin, 10-15% polyimide resin, 1-5% solvent, 1-5% glass powder, 1-10% bicarbonate and 0.5-3% rheological additive.
[0023] In the present invention, a proper amount of bicarbonate is added to the conductive paste. When heated to a certain temperature, the bicarbonate will gradually decompose and generate gas. The generated gas will disturb the conductive paste, and the generated gas will gradually rise, preventing the particles from settling due to the lower viscosity of the conductive paste. Therefore, the conductive paste can maintain good composition stability during the heating process, thereby improving the conductivity and uniformity of the conductive circuit.
[0024] In the present invention, there is no particular limitation on epoxy resin. It is more suitable to use liquid epoxy resin, which can be E-44, E-51, E-12, E-20, etc. The main function is to improve the adhesion and mechanical strength of the conductive paste. Polyimide resin has good thermal stability. The main function is to improve the adhesion and heat resistance of the conductive paste. Thermoplastic polyimide resin can be used, such as liquid polyimide resin or polyimide resin solution (solid content can be 20-80wt%). The solvent is mainly used to adjust the viscosity of the conductive paste to make it more suitable for molding by printing process. For example, the solvent can be acetone, butyl acetate, ethylene glycol dimethyl ether, propylene glycol monomethyl ether, propylene glycol dimethyl ether, etc. Rheological additives are mainly wetting agents, leveling agents, etc., which can improve the wettability of the conductive paste to the substrate and further improve the printing performance. For example, the rheological additive can be a polyether-modified silicone oil, such as Tego 4100, BYK-333, etc.
[0025] In a preferred embodiment of the present invention, the conductive powder is selected from one or a combination of two or more of silver powder, silver-coated copper powder, copper powder, nickel powder, aluminum powder, silver-coated nickel powder and silver-coated aluminum powder. From the resistivity dimension of the conductive powder, the lower the resistivity, the better the conductivity. More preferably, the conductive powder is selected from silver powder, silver-coated copper powder, silver-coated nickel powder and silver-coated aluminum powder. Of course, the conductive powder can also be selected from copper powder. Although the resistivity of copper powder is lower than that of silver powder, the cost is much lower. In some occasions where the conductivity of the conductive circuit is not very high, copper powder can be used. When copper powder is used, copper powder is more susceptible to oxidation than silver powder. The surface of the copper powder can be treated to improve its oxidation resistance. This is reported in multiple prior arts, such as Chinese patents CN118460140A, CN114453578A, CN103128275A, etc.
[0026] In a preferred embodiment of the present invention, the average particle size of the conductive powder is 0.5-10 μm. For example, the average particle size of the conductive powder can be any value of 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc., without any particular limitation.
[0027] In a preferred embodiment of the present invention, the initial melting temperature of the glass powder is not less than 450°C. The curing temperature of high-temperature conductive silver paste is generally around 600°C, at which time the glass powder in the silver paste melts and combines with the glass substrate or silicon substrate and produces good bonding force. Glass powder does not have a definite melting point, and the melting temperature is a temperature range. The present invention finds that when the initial melting temperature of the glass powder is not less than 450°C, it is helpful to remove the organic components, avoid carbonization of the organic components and inability to remove or incomplete removal, and can also better produce preliminary bonding with the glass substrate or silicon substrate, which is beneficial to improve the fixed molding and non-deformation of the conductive circuit. For example, the initial melting temperature of the glass powder can be any value of 450°C, 470°C, 480°C, 500°C, 520°C, 530°C, 550°C, etc., without special restrictions. More preferably, the initial melting temperature of the glass powder is not higher than 550°C.
[0028] In the present invention, the composition of the glass powder is not particularly limited, and may include bismuth oxide, sodium oxide, boron oxide, silicon oxide, calcium oxide, zinc oxide, etc. For example, it may be composed of 10-20% bismuth oxide, 10-20% sodium oxide, 10-15% silicon oxide, 20-30% boron oxide, 1-5% zinc oxide and 30-50% calcium oxide. For example, a specific composition may be 15% bismuth oxide, 10% sodium oxide, 12% silicon oxide, 22% boron oxide, 3% zinc oxide and 38% calcium oxide. The composition of the glass powder can be adjusted to further adjust the melting temperature of the glass powder, including the initial melting temperature.
[0029] In a preferred embodiment of the present invention, the glass powder consists of a first glass powder and a second glass powder;
[0030] The particle size of the first glass powder is 400-500 mesh, and the particle size of the second glass powder is 1000-2000 mesh. The use of two glass powders of different particle sizes and the graded filling of the two glass powders can improve the filling density; the glass powder with a smaller particle size (the second glass powder) has a higher surface activity and a lower melting temperature, so that the melting temperature of the glass powder has a wider temperature range, which is more suitable for the sintering temperature of the slurry, and is more conducive to obtaining a circuit with a good appearance and good conductivity.
[0031] More preferably, the weight ratio of the first glass powder to the second glass powder is 1-10: 1. For example, the weight ratio of the first glass powder to the second glass powder can be any value of 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, etc., without particular limitation.
[0032] In a preferred embodiment of the present invention, the bicarbonate is selected from one or a combination of two or more of sodium bicarbonate, potassium bicarbonate, ammonium bicarbonate, magnesium bicarbonate and calcium bicarbonate. Bicarbonate decomposes and produces gas, such as carbon dioxide, when heated and at a certain temperature, and gradually decomposes and gradually releases gas as the temperature rises. The released gas disturbs the conductive paste and hinders the sedimentation of particles in the paste, avoiding the sedimentation of particles in the conductive paste during the heating process, resulting in uneven paste composition and affecting conductivity. More preferably, the bicarbonate can be selected from sodium bicarbonate, potassium bicarbonate, etc. Sodium bicarbonate and potassium bicarbonate are thermally decomposed to produce carbonates. The thermal decomposition temperature range of sodium bicarbonate is 50-270°C, and the thermal decomposition temperature range of potassium bicarbonate is 100-200°C. Both have a wide thermal decomposition temperature range, can gradually decompose and produce gas as the temperature rises, and the decomposed carbonates (sodium carbonate and potassium carbonate) are highly alkaline, and can produce slight corrosion to the glass substrate or silicon substrate under the action of heat, which is conducive to improving the adhesion of the conductive paste to the substrate. For example, the weight percentage of bicarbonate can be any value among 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc. More preferably, the weight percentage of bicarbonate can be 1-6%.
[0033] In a preferred embodiment of the present invention, the raw material components further include one or a combination of two or more of 0.2-1% defoamer, 0.3-1% coupling agent and 0.2-1% curing agent. Adding a small amount of defoamer to the raw material components can eventually eliminate the bubbles generated after the thermal decomposition of bicarbonate, avoiding the influence of residual bubbles on the performance of the conductive circuit, such as poor conductivity and poor adhesion. For example, the defoamer can be a dimethyl silicone defoamer, and the weight ratio can be 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc. The added coupling agent helps to improve the dispersibility of the conductive powder in the slurry to improve the stability of the conductive slurry, etc. For example, the coupling agent can be a silane coupling agent or a titanate coupling agent, such as methyltrimethoxysilane, tetraethyl titanate, tetrabutyl titanate, etc., and the weight ratio can be 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc. In the present invention, the amount of the curing agent added is controlled, and the curing agent can be slightly cross-linked and cured with the epoxy resin, which plays a preliminary shaping role on the conductive circuit, and avoids the flow and flow of the conductive circuit at high temperature, etc., which affects the shape of the conductive circuit. For example, the weight ratio can be 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc.
[0034] In a preferred embodiment of the present invention, the curing agent is selected from imidazole compounds. Imidazole compounds have the functions of curing agent and accelerator, can slightly crosslink and cure with epoxy resin, and play a preliminary shaping role on the conductive circuit. For example, the imidazole compound can be 2-methylimidazole and the like.
[0035] In the present invention, the preparation method of the conductive paste composition is not particularly limited, and the raw material components can be directly mixed and stirred to disperse. Alternatively, the epoxy resin, polyimide resin, solvent and rheological additive are first mixed evenly, and then the conductive powder is added and mixed evenly, and finally the glass powder and bicarbonate are added and mixed evenly.
[0036] On the other hand, the present invention proposes the use of the conductive paste composition described in any of the above technical solutions, which is applied to silicon-based circuit boards and has good conductivity and adhesion.
[0037] The technical solution of the present invention is further described and illustrated below based on various embodiments and comparative examples.
[0038] Example 1
[0039] The conductive paste composition, based on 100% by weight, comprises the following raw material components: 75% spherical silver powder with an average particle size of 3 μm, 4% epoxy resin E-42, 11.5% polyimide resin solution (solid content 70%), 3% butyl acetate, 3% 450 mesh glass powder (initial melting temperature 530° C.), 2% sodium bicarbonate, 0.5% dimethyl silicone defoaming agent and 1% wetting agent Tego 4100.
[0040] The epoxy resin, polyimide resin solution, butyl acetate, defoamer and wetting agent are mixed evenly, and then spherical silver powder is added, mixed and dispersed evenly, and finally glass powder and sodium bicarbonate are added, mixed and dispersed evenly, and filtered through a 300-mesh filter to obtain a conductive paste composition.
[0041] Example 2
[0042] The difference between this embodiment and embodiment 1 is that the glass powder is changed to 1000 mesh glass powder with the same weight percentage, and the initial melting temperature is 450° C. The other steps remain unchanged.
[0043] Example 3
[0044] The difference between this embodiment and embodiment 2 is that the glass powder is changed to a mixture of 500 mesh glass powder and 2000 mesh glass powder in a weight ratio of 1:1, and the initial melting temperature is 450° C. The other steps remain unchanged.
[0045] The circuit shape after the conductive paste obtained in this embodiment is printed and sintered and cured is as shown in the attached figure. Figure 1 As shown, it can be seen that there is no color difference, no overflow, and no bubbles in the line.
[0046] Example 4
[0047] The difference between this embodiment and embodiment 3 is that the weight ratio of 500 mesh glass powder to 2000 mesh glass powder is adjusted from 1:1 to 5:1. The other steps remain unchanged.
[0048] Example 5
[0049] The difference between this embodiment and embodiment 3 is that the weight ratio of 500 mesh glass powder to 2000 mesh glass powder is adjusted from 1:1 to 10:1. The other steps remain unchanged.
[0050] Comparative Example 1
[0051] The difference between this comparative example and Example 1 is that in Example 1, sodium bicarbonate is not added. The remaining steps remain unchanged.
[0052] Comparative Example 2
[0053] The difference between this comparative example and Example 1 is that in Example 1, sodium bicarbonate is replaced by an equal weight of sodium carbonate. The remaining steps remain unchanged.
[0054] Example 6
[0055] The conductive paste composition, based on 100% by weight, comprises raw material components: 76% spherical silver powder with an average particle size of 5 μm, 3% epoxy resin E-42, 10% polyimide resin solution (solid content 70%), 2.3% ethylene glycol dimethyl ether, 2% 500 mesh glass powder (initial melting temperature 480°C), 5% sodium bicarbonate, 0.7% wetting agent Tego 4100, 0.5% dimethyl silicone defoaming agent and 0.5% 2-methylimidazole.
[0056] Example 7
[0057] The difference between this embodiment and embodiment 6 is that in embodiment 6, 2-methylimidazole is adjusted from 0.5% to 1%, and ethylene glycol dimethyl ether is adjusted from 2.3% to 1.8%. The other steps remain unchanged.
[0058] Example 8
[0059] The difference between this embodiment and embodiment 6 is that in embodiment 6, the sodium bicarbonate is adjusted from 5% to 8%, and the spherical silver powder is adjusted from 76% to 73%. The other steps remain unchanged.
[0060] Comparative Example 3
[0061] The difference between this comparative example and Example 6 is that in Example 6, 2-methylimidazole is adjusted from 0.5% to 3%, ethylene glycol dimethyl ether is adjusted from 2.3% to 1.8%, and sodium bicarbonate is adjusted from 5% to 3%. The remaining steps remain unchanged.
[0062] Performance Testing
[0063] The conductive paste compositions of Examples 1-8 and Comparative Examples 1-3 were screen printed onto a clean silicon substrate surface with a thickness of 25 μm, a line width of 100 μm, and a line spacing of 1 mm. The temperature was raised to 600°C at a heating rate of 5°C / min and maintained for 30 minutes to obtain a conductive circuit. The square resistance, pencil hardness, welding strength (tested by shearing method according to GB / T 28289-2012) and appearance of the conductive circuit were tested. The appearance was visually inspected and divided into 1-5 grades; Grade 5, no overflow of the conductive circuit, no bubbles, and no color difference; Grade 4, one of the conductive circuit overflow, color difference, and bubbles, but it was relatively minor; Grade 3, two or more of the conductive circuit overflow, color difference, and bubbles, but it was relatively minor; Grade 2, at least one of the conductive circuit overflow, color difference, and bubbles was relatively obvious; Grade 1, the conductive circuit overflow, color difference, and bubbles were relatively obvious.
[0064] The results are shown in Table 1 below.
[0065] Table 1
[0066]
[0067] It can be seen from the data results in Table 1 that the conductive paste of the present invention has higher hardness, lower square resistance and higher welding strength after curing. Compared with the case where no bicarbonate is added or carbonate is added, the circuit appearance is better and the square resistance is lower when bicarbonate is added to the raw material components.
[0068] As described above, the basic principles, main features and advantages of the present invention are shown and described. Those skilled in the art should understand that the present invention is not limited by the above embodiments, which are only preferred embodiments of the present invention and cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the scope of the present invention and the contents of the specification should still be within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. A conductive paste composition, characterized in that: Based on 100% by weight, the raw material components include: 50-85% conductive powder, 1-6% epoxy resin, 10-15% polyimide resin, 1-5% solvent, 1-5% glass powder, 1-10% bicarbonate and 0.5-3% rheological additive.
2. The conductive paste composition according to claim 1, characterized in that: The conductive powder is selected from one or a combination of two or more of silver powder, silver-coated copper powder, copper powder, nickel powder, aluminum powder, silver-coated nickel powder and silver-coated aluminum powder.
3. The conductive paste composition according to claim 1, characterized in that: The average particle size of the conductive powder is 0.5-10 μm.
4. The conductive paste composition according to claim 1, characterized in that: The initial melting temperature of the glass powder is not less than 450°C.
5. The conductive paste composition according to claim 1, characterized in that: The glass powder consists of a first glass powder and a second glass powder; The particle size of the first glass powder is 400-500 mesh, and the particle size of the second glass powder is 1000-2000 mesh.
6. The conductive paste composition according to claim 5, characterized in that: The weight ratio of the first glass powder to the second glass powder is 1-10:
1.
7. The conductive paste composition according to claim 1, characterized in that: The bicarbonate is selected from one or a combination of two or more of sodium bicarbonate, potassium bicarbonate, ammonium bicarbonate, magnesium bicarbonate and calcium bicarbonate.
8. The conductive paste composition according to claim 1, characterized in that: The raw material components further include one or a combination of two or more of 0.2-1% defoamer, 0.3-1% coupling agent and 0.2-1% curing agent.
9. The conductive paste composition according to claim 1, characterized in that: The curing agent is selected from imidazole compounds.
10. Use of the conductive paste composition according to any one of claims 1 to 9, characterized in that: Applied to silicon-based circuit boards.
Citation Information
Patent Citations
Anti-oxidation method for superfine copper powder
CN103128275A
Flexible high-temperature-resistant conductive paste
CN113555145A
Modified copper powder, modification method thereof and conductive paste
CN114453578A
Preparation method of antioxidant copper powder and copper powder conductive adhesive
CN118460140A